Biological research on addiction - Miller, Peter M. (Peter Michael), 1942- (Comprehensive addictive behaviors and disorders, 2013)
The volume presents current material on the key neurobiological and genetic elements in an individual's susceptibility to drug dependence as well as the processes by which some individuals proceed from casual drug use to drug dependence. Chapters describe and explain the neurobiological mechanisms of drug use and drug addiction. The development and use of animal models to study neurochemical, molecular and cellular brain mechanisms are described and illustrated. Other chapters discuss the effects of drug use on memory, decision-making, and the developing brain (especially in adolescents).